Individual learning behavior: do all its dimensions matter for selfemployment practice among youths in Uganda? - Balunywa, Waswa; Kusemererwa, Christopher; Munene, John C.; Laura, Orobia A. (Emerald publishing company, 2020)
Purpose – The purpose of this paper is to establish whether all the dimensions of individual learning behavior matter for self-employment practice among youths, using evidence from Uganda. Design/methodology/approach – This study is a correlational and cross-sectional type. A questionnaire survey of 393 youths was used. The data collected were analyzed through SPSS. Findings – The results indicate that meaning-oriented learning behavior, planned learning behavior and emergent learning behavior do matter for self-employment practice among youths in Uganda unlike instruction-oriented learning behavior. Research limitations/implications – This study focused on self-employed youths who have gone through tertiary education in Uganda. Therefore, it is likely that the results may not be generalized to other settings. The results show that to promote self-employment practice among youths, the focus should be put mainly on meaning-oriented learning behavior, planned learning behavior and emergent learning behavior. Originality/value – This study provides initial evidence on whether all the dimensions of individual learning behavior do matter for self-employment practice among youths using evidence from an African developing country – Uganda.
Keywords: Self-employment; Individual learning behavior; Meaning-oriented learning behavior; Instruction-oriented learning behavior; Planned learning behavior; Emergent learning behavior